Pengaruh Green Marketing dan Consumer Knowledge Terhadap Brand Image Produk Tupperware - Meri Ariani; Rose Rahmidani (Universitas Negeri Padang, 2020)
This study aims to reveal the effect of green marketing and consumer knowledge towards brand image of Tupperware in Padang. This type of research is causative. The population of this research are people who use Tupperware. The sample of this research is based on Chocran formula of 100 respondents that choose by using Nonprobability sampling methods and purposive sampling technic. It used primary data that obtained through distributing questionnaires to people in Padang with particular criteria. This research is using multiple regression analysis as method of analysis with SPSS 26. The result of this research is show that (1) Green marketing has significant effect towards the brand image of Tupperware in Padang (2) Consumers knowledge has significant effect to brand image of Tupperware in Padang. Keywords: green marketing, consumer knowledge, brand image